Assessing the management system to demonstrate the safe of transport of radioactive material (Brazilian Journal of Radiation Sciences, 2021)
Radioactive materials are used for medical purposes, to avoid greenhouse gas effect in energy production plants, food and other products sterilization, research and sophisticated measurement technologies. Transport of radioactive material involves a range of actors each one having specific responsibilities for safety. Through Management System, consignors and carriers fulfil objective evidences that safety requirements are met in practice, while compliance assurance programs allow regulatory bodies and/or competent authorities to demonstrate to society that public, workers and environment are protected. According to IAEA, safety has to be achieved and maintained through an effective management system. This system should integrate all elements of management so that requirements for safety are established and applied consistently with other requirements, including those related to human performance, quality and security, and so that safety is not committed by other requirements or demands. CNEN, the Brazilian Regulatory Body for the safe transport of radioactive materials, adopt international standards to establish safety requirements deemed relevant for protection of health and minimization of danger to life and property, and to provide for the application of these standards. Seeking for continuous improvement, the adherence of the practices adopted by Transport Safety Unit (TSU) against the recommendations from the IAEA was assessed. This assessment led to the elaboration of proposals for improvement as well as the identification of good practices. The methodology used to perform this assessment was the SARIS methodology, developed by the IAEA. This paper will describe the most relevant findings of this study.